Induction of labour: a comparative study of dinoprostone gel versus vaginal misoprostol versus sequential intracervical Foley’s catheter followed by vaginal misoprostol versus concurrent intracervical Foley’s and dinoprostone gel - Kaur, Prabhjot; Grover, Suparna; Goyal, Shreeji; Kaur, Ibadatpreet (International Journal of Research in Medical Sciences, 2025)
Background: Induction refers to the stimulation of contractions prior to the spontaneous commencement of labour, whether or not the membranes have already ruptured. Induction of labour is needed when risks outweigh the benefits of pregnancy continuation and there is no contraindication for vaginal delivery. Methods: This was a randomized control trial which included low risk pregnant women at term gestation. Eligible patients were divided into 4 groups by randomisation in ratio of 1:1:1:1 with 25 patients in each group i.e. vaginal misoprostol (25 µgm) (group A) versus intracervical dinoprostone gel (group B) versus sequential intracervical Foley’s catheter followed by vaginal misoprostol (group C) versus concurrent intracervical Foley’s and dinoprostone gel. Results: Use of dinoprostone gel for cervical priming is a more efficacious method among women needing labour induction with bishop score <6 compared to vaginal misoprostol, concurrent intracervical foley’s as well as sequential intracervical Foley’s and vaginal misoprostol. It is associated with higher rates of vaginal delivery (84%, p value 0.001), shortened induction delivery interval (14.38±7.16 hours, p value 0.178) and least risk of fetal distress/MSL. Conclusions: Use of dinoprostone gel for cervical priming is a more efficacious method as it is associated with higher rates of vaginal delivery, more predictable response, shortened IDI and least risk of fetal distress/MSL. It should be preferred over tablet vaginal misoprostol especially for nulliparous women.